Reflexivity and Subjectivity: A Dialogical Perspective for and on International Relations Theory - Xavier Guillaume (Forum: Qualitative Social Research, 2002)
The aim of this essay is to discuss the places of the notions of subjectivity and reflexivity within International Relations (IR) theory by contrasting the classical perspective inspired by positivism with a dialogical perspective which tries to fully integrate these notions in its examination of the specific nexus between identity and alterity. This dialogical perspective proposes a reflexive tool, the hermeneutical locus, which is intended to provide a way to assess the subjectivity of the cognised without falling into reification and a reflexive archaeology of the discipline of IR itself. In this sense, a dialogical approach wishes to offer a reflexive tool for and on IR theory. URN: urn:nbn:de:0114-fqs0203133